Studi Kemauan Membayar (Willingness To Pay) Masyarakat Permukiman Kumuh di Kelurahan Kemijen untuk Mendapatkan Air Bersih - Vita Wahyu Utami; Agung Sugiri (Jurusan Perencanaan Wilayah dan Kota, 2022)
People in the slum areas struggle to survive by using their limited income to get clean water. Those who face problems with the provision of clean water have their own assessment of environmental goods, in this case clean water. The research tries to identify how much people are willing to pay for clean water if they are faced with the opportunity to get better clean water. This study aims to estimate the amount of community WTP in the provision of clean water and to analyze the factors that influence the WTP in Kemijen Sub-district, Semarang City. The method used is the congtingent valuation method (CVM) to estimate the cost desired by the community and logistic regression analysis to identify the factors that influence the community in paying. The data needed in the study were obtained through a questionnaire. From the analysis, the factors that significantly influence the WTP of the community in paying water are the level of education, number of family members, and community knowledge. The WTP value obtained is Rp313/m3. The results of this study can be used by stakeholders in considering the planned clean water supply service system along with the estimated tariff that will be applied.